Correlation Between Knee Osteoarthritis Pain and The Ability to Perform Salat - Aisyah; Pane, Rita Vivera; Ambarasari, Utami; Kartini, Yanis (UNUSA Press, 2024)
Introduction: Osteoarthritis (OA) has affected approximately 303 million individuals worldwide, making it the second most rapidly increasing disease behind Rheumatoid Arthritis. OA is the leading cause of lower extremity disability amongst older adults with an estimated lifetime risk for knee OA being approximately 40% in men and 47% in women. Osteoarthritis affects the entire joint which has symptoms that could intense pain and discomfort, making it difficult to carry out typical routine activities. This, of course, will conflict with Muslims who are obligated to perform daily prayers or salat which is an obligatory component of the daily routine of Muslims that is performed in the same way at least five times a day. Objective: This study aimed to analyze the correlation between knee osteoarthritis pain and the ability to perform salat. Methods: The method used in this study is an analytic observational method with a random sampling technique which was involved by 57 respondents in total. The data obtained was collected from April to May and showed frequency and percentage. Determination of the correlation between Knee Osteoarthritis and The Ability to perform Salat is done by statistical analysis with chi-square test using the SPSS application. Results: The asymptotic value obtained was 0.238. The obtained asymptotic value is >0.05. Conclusions: It can be concluded that there is no significant correlation between knee osteoarthritis pain and the ability to perform salat movements.